Prospects of COVID-19 Vaccination in Romania: Challenges and Potential Solutions - Dascalu, Stefan; Geambasu, Oana; Covaciu, Ovidiu; Chereches, Razvan Mircea; Diaconu, Gabriel; Dumitra, Gindrovel Gheorghe; Gheorghita, Valeriu; Popovici, Emilian Damian (Frontiers in Public Health, 2021)
The rapid advancement in vaccine development represents a critical milestone that will help humanity tackle the COVID-19 pandemic. However, the success of these efforts is not guaranteed, as it relies on the outcomes of national and international vaccination strategies. In this article, we highlight some of the challenges that Romania will face and propose a set of solutions to overcome them. With this in mind, we discuss issues such as the infrastructure of vaccine storage and delivery, the deployment and administration of immunisations, and the public acceptance of vaccines. The ways in which Romanian society will respond to a national COVID-19 vaccination campaign will be contingent on appropriate and timely actions. As many of the problems encountered in Romania are not unique, the proposed recommendations could be adapted and implemented in other countries that face similar issues, thereby informing better practices in the management of the COVID-19 pandemic.